Fasting plasma glucose and HbA1c levels predict the risk of type 2 diabetes and diabetic retinopathy in a Thai high-risk population with prediabetes - Washirasaksiri, Chaiwat; Srivanichakorn, Weerachai; Borrisut, Nutsakol; Sitasuwan, Tullaya; Tinmanee, Rungsima; Kositamongkol, Chayanis; Ariyakunaphan, Pinyapat; Auesomwang, Chonticha; Sayabovorn, Naruemit; Chaisathaphol, Thanet; Phisalprapa, Pochamana (Frontiers in Pharmacology, 2022)
Introduction: The incidences of diabetes and diabetic retinopathy (DR) in Thai high-risk individuals with prediabetes have not been identified. This study compared diabetes and DR incidences among people at risk with different glycemic levels, using fasting plasma glucose (FPG) and hemoglobin A1C (HbA1c). Materials and methods: A historical cohort study estimating risk of type 2 diabetes and DR was conducted among outpatients, using FPG and HbA1c measurements at recruitment and monitored for ≥ 5 years. High-risk participants (defined as having metabolic syndrome or atherosclerotic cardiovascular disease) were categorized by glycemic level into 4 groups: (1) impaired fasting glucose (IFG)-/HbA1c- (FPG < 110 mg/dL; HbA1c < 6.0%); (2) IFG+/HbA1c- (FPG 110–125 mg/dL; HbA1c < 6.0%); (3) IFG-/HbA1c+ (FPG < 110 mg/dL; HbA1c 6.0%–6.4%); and (4) IFG+/HbA1c+ (FPG 110–125 mg/dL; HbA1c 6.0%–6.4%). The incidences of type 2 diabetes mellitus (T2DM) and DR were obtained and estimated using Kaplan–Meier analysis. Cox regression models explored hazard ratios (HRs). Results: We recruited 8977 people at risk (metabolic syndrome, 89.9%; atherosclerotic cardiovascular disease, 16.9%). The baseline cohort consisted of (1) IFG-/HbA1c- (n = 4221; 47.0%); (2) IFG+/HbA1c- (n = 1274; 14.2%); (3) IFG-/HbA1c+ (n =2151; 24.0%); and (4) IFG+/HbA1c+ (n = 1331; 14.8%). Their 5-year T2DM incidences were 16.0%, 26.4%, 30.8%, and 48.5% (P < 0.001). The median DR follow-up was 7.8 years (interquartile range, 7.0–8.4 years). The DR incidences were 0.50, 0.63, 1.44, and 2.68/1000 person-years (P < 0.001) for IFG-/HbA1c-, IFG+/HbA1c-, IFG-/HbA1c+, and IFG+/HbA1c+, respectively. Compared with IFG-/HbA1c-, the multivariable-adjusted HRs (95% CI) for incident diabetes were 1.94 (1.34–2.80), 2.45 (1.83–3.29), and 4.56 (3.39–6.15) for IFG+/HbA1c-, IFG-/HbA1c+, and IFG+/HbA1c+, respectively. As for incident DR, the corresponding HRs were 0.67 (0.08–5.76), 4.74 (1.69–13.31), and 5.46 (1.82–16.39), respectively. Conclusions: The 5-year incidence of T2DM in Thai high-risk participants with prediabetes was very high. The incidences of diabetes and DR significantly increased with higher degrees of dysglycemia. High-risk people with FPG 110–125 mg/dL and HbA1c 6.0%–6.4% were more likely to develop T2DM and DR. Such individuals should receive priority lifestyle and pharmacological management.